Mendorong Keterlibatan Remaja dalam Pelayanan melalui Penguasaan Alat Musik Gereja di GKSI Petra Mappai - Walde Mesah (Universitas 45 Surabaya, 2025)
The involvement of youth in church ministry is a crucial aspect for the sustainability of faith and the growth of the congregation. This article discusses efforts to increase youth participation in GKSI Petra Mappai through training in musical instruments, especially keyboards, as a means of service and character building. The training is designed in a participatory and educational manner, with a fun and targeted approach to fit the dynamics of adolescents. The results of the activity showed that participants not only gained technical skills in playing music, but also experienced development in aspects of discipline, responsibility, cooperation, and service spirit. The documentation of the activity shows significant progress from the initial stage of training to the active involvement of adolescents in accompanying worship. These findings confirm that music can serve as an effective medium to build faith, strengthen togetherness, and foster a commitment to service within the church community. Music training has proven to be a relevant and contextual strategy in preparing a faithful, skilled, and integrity young generation to continue church ministry. Thus, this approach can be an inspirational model for other churches in developing the potential of young people as active and impactful servants of God.